Antioxidant activity and sun protection factor evaluation for cream formulation of purified roasted corn silk extracts (Zea Mays L. Saccharata) - Munifatul Lailiyah; Sony Andika Saputra; Fita Sari (Pharmaciana, 2020)
Free radicals might cause harmful effects on the skin, such as skin irritation, change of skin color, and worst effect. Phenolics play a role as effective sunscreen and antioxidants to prevent UV radiation effects. Corn silk contains flavonoids, which are antioxidants that are potential as sunscreen. Phenolic compounds can be identified by phytochemical screening using the tube method. The study aims to know the antioxidant activity of purified extract of roasted corn silks (Zea Mays L. saccharata) and know the SPF level of the cream preparation. The study was conducted by collecting samples of roasted corn silks waste to make dried simplicial, then extracting it with 70% ethanol as solvent, evaporated till condensed extract is gotten. The obtained extract was then purified with n-hexane solvent. The antioxidant activity test was conducted by using the DPPH method. The cream of the purified extract was made in three formulations: 1%, 5%, and 10% concentration. Its SPF levels were then evaluated. The results showed the purified corn silks extract had an IC50 value of 256.66 µg/mL better compared to corn silks ethanol extract having an IC50 value of 356.17 µg/mL including the weak antioxidant category. Meanwhile, the SPF level test results for concentration of 1%, 5%, and 10% are 1.27 ; 2.41; and 5.94 respectively.